Changing Labor and Delivery Practice: Focus on Achieving Practice and Documentation Standardization with the Goal of Improving Neonatal Outcomes. (21st October 2016) - Burstein, Paul D.; Zalenski, David M.; Edwards, John L.; Rafi, Ishrat Z.; Darden, Jennifer F.; Firneno, Cassandra; Santos, Palmira
Abstract : Objective: To establish multifactorial shoulder dystocia response and management protocol to promote sustainable practice change. Data Sources/Study Setting: Primary data collection was conducted over 3 years. Implementation of the protocol spanned 13 months. Data collection occurred at five sites, which were chosen for their diversity in both patient mix and geographical location. Study Design: Case study evaluation methodology was used to examine clinician engagement and protocol adoption. Data Collection Methods: The training completion for all practice engagement team activities was collected by the site project manager and entered into a flat file. Data from the labor and delivery notes, medical records, and interviews with labor and delivery teams were gathered and analyzed by the senior investigator. Principal Findings: In the first year, there was a threefold increase in shoulder dystocia reporting, which continued in years 2 and 3. In the first year, 96 percent of clinicians completed all training elements and in subsequent years, 98 percent completed the follow‐up training. Overall teams reached a 99 percent adoption rate of the shoulder dystocia protocol. Conclusions: System and site management teams implemented a standardized shoulder dystocia protocol that fostered effective teamwork and obstetric team readiness for managing shoulder dystocia emergencies.